Magnetism induced by excess electrons trapped at diamagnetic edge-quantum well in multi-layer graphene - Zhang, Xi (2014)
In this paper, we clarified a robust mechanism of magnetism generated by excess electrons captured by edge-quantum well of diamagnetic armchair edges. Consistency between density functional theory calculations and electron cyclotron resonance experiments verified that: (1) Multi-layer armchair nanoribbons are stable with proper amounts of excess electrons which can provide net spin; (2) Since under-coordination induces lattice relaxation and potential well modulation, electrons tend to be trapped at edges; and (3) Neither large amount of excess electrons nor positive charges can induce magnetism. This work shed light on the development of graphene devices in its magnetic applications.